#TITLE_ALTERNATIVE# - AKBAR (NIM : 10212099), ALI
The nanofibers synthesis process that using rotary forcespinning method utilizes the motor rotational speed to provide centrifugal force to the solution in the reservoir so that the solution is thrown out through the nozzle. Brushless DC (BLDC) motor is used to rotate the rotary forcespinning reservoir by using PID control system to achieve certain rotation speed. To determine the PID control parameter, tuning process is done by using second method of Ziegler-Nichols rule. Then some test is done for different types of controller such as classic PID, PID with some overshoot, and PID with no overshoot. For nanofibres synthesis precursor, a solution of styrofoam with concentration 28%(w/w) is used with solvent d'limonene. Variations of motor rotational speed and size of syringe nozzle are performed to see the relationship between the rotational speed and the nozzle size with diameter of resulting fibers. The fibers that formed in the collector will be observed under a microscope and measured by taking one hundred fiber diameter data to see the fiber distribution. From the experiment results, all fibers have a coeffcient of variation below 0.3 and have diameter range between 2 m and 12 m. The greater rotational speed causing the resulting fibers have smaller average diameter, while the larger size of syringe nozzle causing the resulting fibers have greater average diameter.